Failure Mechanisms and Mitigation Measures of the G1006 Electricity Pylon Landslide in the Dam Area of the Jinping I Hydropower Station. Issue 2 (October 2020) - Yang, Y X; Luo, G; Duan, Y Y; Zhang, C Z; Zhang, Y G; Lei, Q
Abstract: On the 29th and 30th of August 2012, more than 100 geological disasters occurred near the dam area of Jinping I Hydropower Station, Xichang, China due to local intense rainstorm. The upper part of the left valley slope, which is 500 m upstream of the dam, failed and slid, exposing the C-pile of the G1006 electricity pylon and threatening the entire power transmission lines. Therefore, ensuring the stability of the residual rock masses in the rear of the main scarp and the safety of the G1006 electricity pylon became a primary emergency task. Field geological survey, topographic mapping, and the instability mechanism study of the G1006 electricity pylon landslide were conducted. Results revealed that the G1006 electricity pylon landslide (here after represented as the G1006 EPL) occurred in the middle block cut by two faults, and the rock masses had inferior mechanical properties. Intense unloading effects and frequent microseism events during the dam construction relaxed the rock mass structural planes and reduced the geotechnical parameters. Under the influence of intense rainfall, the failure mechanisms of the slope were a combination of slope surface effect from rainfall and lateral erosion and undercutting of the slope toe by high flooding. The residual rock masses and landslide deposits around the pylon foundation were unstable under natural conditions and during the rainstorm. To prevent the continuous damage and exposure of C-pile foundation and ensure the stability of pylon foundation, the mitigation measure of "retaining piles + platform + retaining wall" was arranged. Moreover, a check dam was added to stabilize the slope toe and prevent the landslide deposits, which are the starting material source of debris flow that threatens the safety of the arch dam.